The effect of batik occupational therapy on reducing hallucination symptoms in schizophrenia patients - Akbar, Faliza Aidul; Pratiwi, Arum (Science Midwifery, 2025)
Hallucinations are the main symptom in patients with schizophrenia. Based on several studies found that most patients with schizophrenia experience hallucinations. One of the modality therapies to reduce hallucinations in patients with schizophrenia is occupational therapy. This study aims to determine the effect of batik occupational therapy on reducing signs of hallucination symptoms. This type of research is descriptive with a before after study approach. The sample of this study amounted to five patients with adult patient criteria, treated at least the fifth day, hearing voices and cooperative. The data analysis used is the paired t test. The results of the analysis showed that the average percentage of the five subjects after being given batik occupational therapy was a score of 3.6 (45%) from an average score of 4.4 (55%) to a score of 5 (100%), and there was a difference in auditory hallucinations between pretest and posttest scores in schizophrenia patients with a t of -3.930 and a P value of 0.002. The conclusion of this study is that batik occupational therapy can successfully reduce the symptoms of auditory hallucinations.